Analysing attitude, interaction and counteraction towards fake news on twitter of international relation realms - HELAL ALKHATERI, SHAIKHA MOHAMMED ALI (2022)
Social media is increasingly popular globally, and in the United Arab Emirates (UAE), Twitter, in particular, is used to follow and share news. This has created new areas of risk, as the spread of fake news has led to new and previously unknown threats to international relations and public diplomacy. The UAE has developed a number of initiatives to combat the threat of fake news, however, there is limited formal research into these efforts, particularly from the government perspective. This research represents an initial, explorative look into the issue of fake news on Twitter in relation to international relations from the UAE government perspective. The research objectives included: to analyse the government attitude towards Twitter and fake news in terms of international relations, to investigate the government interaction with Twitter regarding the measures taken in combating the fake news spread in terms of international relations, and to investigate the effectiveness of the measures taken to combat the spread of fake news in terms of international relations. The research used an exploratory, descriptive quantitative method, including a secondary literature review. The survey was developed considering the variables of attitude, interaction and counteraction; and was administered online towards selected top officials of a range of public organizations. A secondary literature review pillared the survey, and also included data from government publications regarding laws or entities that address fake news which was used to help answer the research questions. The collected data was statistically analyzed, with results indicating that Twitter plays an important role in the UAE government and fake news; that the government has instituted legal penalties as well as created dedicated agencies or departments to combat the spread of fake news; and that such efforts have been effective, in particular, the penal provisions imposed on offenders. Recommended future efforts include the establishment of gatekeepers and other systems to monitor and detect fake news, the development of awareness campaigns, and other legislative means such as increased fines and imprisonment to limit the creation and/or spread of fake news. The phenomenon of fake news in relation to international relations is relatively new, and there is a gap in the literature on this topic particularly in the UAE context and from the government perspective. Therefore, this research offers an important contribution as it gives a preliminary view from the main stakeholder (government) in the research into social media, fake news, governance and international relations, which is under-represented in the literature.